2018
DOI: 10.1038/s41598-018-30296-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of immunotherapy and standard therapy in patients with high grade glioma: a meta-analysis of published clinical trials

Abstract: Immunotherapy holds great promise in the treatment of high grade glioma (HGG). We performed a comprehensive meta-analysis of clinical trials involving dendritic cell (DC) therapy and viral therapy (VT) for the treatment of HGG, in order to assess their clinical impact in comparison to standard treatments in terms of overall survival (OS) and progression-free survival (PFS). To our knowledge, this is the first meta-analysis to evaluate VT for the treatment of HGG, allowing comparison of different immunotherapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…Systematic reviews and meta-analysis studies of phase I-II clinical trials demonstrated that the addition of dendritic cell vaccines to standard therapy improved the median overall survival and 2- and 3-year survival rates of patients with newly diagnosed or recurrent high-grade gliomas [145,146,147,148,149]. Recent early phase clinical trials largely supported these conclusions (Table 3).…”
Section: Dendritic Cell/peptide Vaccines and Car T-cells For Gliobmentioning
confidence: 97%
“…Systematic reviews and meta-analysis studies of phase I-II clinical trials demonstrated that the addition of dendritic cell vaccines to standard therapy improved the median overall survival and 2- and 3-year survival rates of patients with newly diagnosed or recurrent high-grade gliomas [145,146,147,148,149]. Recent early phase clinical trials largely supported these conclusions (Table 3).…”
Section: Dendritic Cell/peptide Vaccines and Car T-cells For Gliobmentioning
confidence: 97%
“…In recent years, immunotherapies have gained much research attention, and more evidence shows that high-grade gliomas can obtain benefits from the use of immunotherapies [9]. Six meta-analyses published between 2014 and 2018 indicated that improved OS and PFS were obtained via administration of immunotherapy in HGG patients [10][11][12][13][14][15]. To the best of our knowledge, ours is the first meta-analysis to include such detailed subgroup analyses.…”
Section: Introductionmentioning
confidence: 93%
“…A number of new immunotherapeutic approaches have been recently developed and examined in GBM. These include immune checkpoint inhibitors, chimeric antigen receptor (CAR) T-cells, and dendritic cell/peptide vaccines (reviewed in [64][65][66][67]). While these approaches show considerable promise, they all currently remain in clinical trials, with the immunosuppressive tumor microenvironment of GBM representing a major barrier.…”
Section: Advances In Treatments For Gbmmentioning
confidence: 99%